Models and Methods for Planning Hydrogen Supply Chain Systems - Han Liu; Jing Ma (CSEE Journal of Power and Energy Systems)
Hydrogen is becoming an important candidate for replacing fossil fuels in the future energy economy. As such, efficient hydrogen supply chain system planning and the promotion of its large-scale civilian and commercial applications are needed. To identify research gaps in the field, this study reviews models and methods for planning hydrogen supply chain systems that have been employed over the past 15 years. Significant decision aspects and objectives in the hydrogen supply system are presented. Thereafter, problem types, modeling techniques and solution methods are analyzed and classified based on their individual characteristics. Finally, potential directions promoted by economic factors are recommended for future research.